COVID-19 Risk Perception, Trust in Institutions and Negative Affect Drive Positive COVID-19 Vaccine Intentions - Musa, Sanjin; Cilovic-Lagarija, Seila; Kavazovic, Ariana; Bosankic-Cmajcanin, Nina; Stefanelli, Alberto; Scott, Nadia Aleyna; Scherzer, Martha; Kiss, Zsolt; Bach Habersaat, Katrine (International Journal of Public Health, 2022)
Objectives: To investigate country-specific drivers and barriers of positive COVID-19 vaccine intentions in the Federation of Bosnia and Herzegovina (FBiH), one of the two entities comprising Bosnia and Herzegovina. Methods: A cross-sectional study design was used, using an online behavioural insights survey tool adapted to the context of FBiH. Three survey waves, each including approximately 1000 adults, were conducted in July, September and December 2020. Fixed-effects regression analysis was used to explore the drivers, barriers and attitudes towards accepting a future COVID-19 vaccine. Results: COVID-19 risk perception, trust in health institutions and negative affect were positive predictors of positive COVID-19 vaccine intentions, as were living in urban areas and having a college education (versus having primary or secondary education). Conversely, being female, feeling that the pandemic was overhyped by the media and the country of vaccine production (the Russian Federation or China) were negative predictors. Conclusions: This study provided snapshots on the state of attitudes regarding a future COVID-19 vaccine acceptance and hesitancy in 2020. Further efforts should focus on better understanding the demographic, cultural and behavioural contexts.